Uji Antagonisme Tiga Isolat Fungi Endofit Anggrek Bulan Terhadap F. Oxysporum Secara in vitro - Khaterine K; Rina Sri Kasiamdari (Biogenesis: Jurnal Ilmiah Biologi, 2016)
Phalaenopsis amabilis (L.) Blume or Moth Orchid is Indonesia’s native orchid. In its cultivation, the crown rot which is caused by F. oxysporum is one of diseases that usually attack P. amabilis. The aim of this research is to assess the potency of endophytic fungi Sistotrema sp., Ceratorhiza sp. and Moniliopsis sp., that were isolated from healthy P. amabilis roots, in inhibiting F. oxysporum growth in vitro. The experiment of antagonist test was arranged in complete randomized design by three replications. The in vitro antagonist test was done on PDA and the parameter was the percentage inhibitation of F. oxysporum growth by endophytic fungi. The collected data were analyzed by one way anova and DMRT. The result showed that the three endophytic fungi isolated from P. amabilis roots had the potency in inhibiting F. oxysporum. In vitro antagonism test result showed that Moniliopsis sp. had the highest inhibition percentage (71,80%) among Ceratorhiza sp. (67,70%) and Sistotrema sp. (54,87%).